Risk factors for cytomegalovirus disease in seropositive renal transplant recipients; a single-center case-controlled study - Viviana Navarro-Rodríguez; Alvaro Herrera-Munoz; Adrián Castro; Allan Ramos-Esquivel (Society of Diabetic Nephropathy Prevention, 2017)
Background: Risk factors for cytomegalovirus (CMV) disease in renal transplant recipients have been evaluated in industrialized countries with relatively low CMV seroprevalence. Objectives: We aimed to determine which factors are related to this illness in a high CMV seroprevalence country. Patients and Methods: A case-control study was performed with data from a 5-year follow-up of 260 kidney transplant recipients at our center. Odds ratios were calculated using the Mantel-Haenszel method. Results: A total of 25 cases of CMV disease occurred during the study period. Recipient age greater than 55 years old (odds ratio: 4.95, 95% CI: 1.44-17.0) and use of thymoglobulin (odds ratio: 4.84; 95% CI: 1.10-21.39) were the only independent predictors for CMV disease. There was not any relationship between the previous serologic status of both donor and receptor and the occurrence of CMV disease. We did not observe any association between the immunosuppressive regimens and CMV disease, except for thymoglobulin. Conclusions: Only recipient age and thymoglobulin administration were related to CMV disease. Further studies are needed to determine if prophylactic treatment confers clinical benefit in this subset of patients.